ART-THERAPEUTIC TECHNOLOGIES AS CORRECTION AND REGULATORY MEANS FOR SENSORY INTEGRATION DISORDERS (EDUCATION IN THE 21ST CENTURY, 2023)
The collection and processing by the brain of a large amount of information about our daily sensations as a result of the nervous process, their generalization and activation of various sensory signals using healthy nervous processes is a complex system of processes through which a person lives and acts, reacts to the environment. Sensory integration is the exact location of different sensations. The causes of sensory integration disorders may be different, they require detailed study and elimination, because such disorders can interfere with the child's socialization process and cause serious problems in the future.From this point of view, it is of interest to study sensory integration as a systemic process in which the human nervous system receives information about the world around it through all the senses and reacts to them by collecting, regulating, processing the collected information and applying it to other purposeful activities. The underdevelopment or violation of any of them prevents the complete collection of necessary information. It delays or does not form adaptive reactions to the phenomenon, which complicates the relationship between the child and the outside world.Art technologies can play a very important role in solving or resolving this problem. It can be divided into categories depending on the problem and/or depending on the lack of sensory stimulation. The main objective of our research is aimed at studying sensory integration disorders, as well as the prevention of defects using artificial technologies.
Keywords: sensory integration; sensory disorder; adaptive skills; art technologies; levels of sensory interaction